2014
DOI: 10.1371/journal.pntd.0002615
|View full text |Cite
|
Sign up to set email alerts
|

Animal Reservoir, Natural and Socioeconomic Variations and the Transmission of Hemorrhagic Fever with Renal Syndrome in Chenzhou, China, 2006–2010

Abstract: BackgroundChina has the highest incidence of hemorrhagic fever with renal syndrome (HFRS) worldwide. Reported cases account for 90% of the total number of global cases. By 2010, approximately 1.4 million HFRS cases had been reported in China. This study aimed to explore the effect of the rodent reservoir, and natural and socioeconomic variables, on the transmission pattern of HFRS.Methodology/Principal FindingsData on monthly HFRS cases were collected from 2006 to 2010. Dynamic rodent monitoring data, normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 26 publications
1
53
1
Order By: Relevance
“…These models predicted HFRS incidence one-month-ahead with pseudo-R 2 values of 81–82%. These results are valuable since they point the way to an early warning signal prior to potential HFRS outbreaks via increases in rodent density or rainfall [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These models predicted HFRS incidence one-month-ahead with pseudo-R 2 values of 81–82%. These results are valuable since they point the way to an early warning signal prior to potential HFRS outbreaks via increases in rodent density or rainfall [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rodents are the predominant reservoir of hantavirus and excrete virus-containing urine, feces, and saliva when chronically infected. Humans usually become infected with hantaviruses through contact with or inhalation of aerosols and secretions from infected rodent hosts [ 4 ].The external environmental factors, including temperature, rainfall, relative humidity, NDVI, elevation and land use, not only affect the rate of replication of virus, but also have an impact on disease reservoir-rodents and contact between the human and rodent populations [ 5 ], which eventually affects HFRS incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in different areas of China and other countries have suggested that external environmental factors, including natural factors (such as temperature [ 6 , 7 , 8 ], precipitation [ 4 , 5 , 9 ], humidity [ 7 ], normalized difference vegetation index (NDVI) [ 10 , 11 ] and elevation [ 6 ]) and social-economic factors (such as land use [ 6 , 12 ]), may affect the incidence of HFRS. These factors may differentially influence the incidence of HFRS in different regions because of the spatiotemporal heterogeneity in climate types, ecological characteristics, population immunity, public health intervention measures, and socioeconomic factors within different regions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…HFRS, a serious zoonotic disease caused by hantaviruses, can be transmitted to humans by contact with infected rodents or their excreta . The disease is frequently reported in China where roughly 90% of the world's cases occur (Xiao et al, 2014). Although the incidence of HFRS significantly declined during the 1990s, there has been an increasing trend since 2008 (Xiao et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is frequently reported in China where roughly 90% of the world's cases occur (Xiao et al, 2014). Although the incidence of HFRS significantly declined during the 1990s, there has been an increasing trend since 2008 (Xiao et al, 2014;Zhang et al, 2014). The possible reasons for the emergence and re-emergence of these infectious diseases may be linked to climate change, population movement, rapid urbanization and increased surveillance efforts (Tong et al, 2015;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%